2016
DOI: 10.1097/mpg.0000000000001123
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab Dosing Strategies and Predicted Trough Exposure in Children With Crohn Disease

Abstract: Objectives Standard infliximab maintenance dosing of 5 mg/kg every 8 weeks may be inadequate to consistently achieve sufficient drug exposure to minimize loss of response or treatment failure in pediatric Crohn’s disease (CD). We aimed to determine the predicted infliximab trough concentrations in children with CD during maintenance therapy and the percentage of patients achieving target trough concentration >3 μg/ml. Methods A Monte Carlo simulation analysis was constructed using a published population phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 27 publications
1
29
2
Order By: Relevance
“…The trough levels during induction were higher during 2016, and it is very likely that this reflects a change in clinical practice during this period, as studies carried out around this time reported better responses in young children with higher doses. 16,17 Disappointingly, although the trough levels during induction were higher, we did not observe any increase in the proportion of patients that maintained their therapeutic response. There were no major adverse events during the study period, no alarming signs and no acute infusion reactions with either of these drugs.…”
Section: Discussioncontrasting
confidence: 62%
“…The trough levels during induction were higher during 2016, and it is very likely that this reflects a change in clinical practice during this period, as studies carried out around this time reported better responses in young children with higher doses. 16,17 Disappointingly, although the trough levels during induction were higher, we did not observe any increase in the proportion of patients that maintained their therapeutic response. There were no major adverse events during the study period, no alarming signs and no acute infusion reactions with either of these drugs.…”
Section: Discussioncontrasting
confidence: 62%
“…The pharmacokinetics of infliximab are highly variable in this population and consequently dose requirements will vary between patients. (3,11) In the cohort of children examined in the current study, the predicted infliximab maintenance dosing strategy needed to achieve a trough concentration >3 μg/ml was quite heterogeneous and ranged from the standard dosing of 5 mg/kg every 8 weeks up to 5 mg/kg every 4 weeks (Figure 3A). Our cohort was homogenous in terms of serum albumin (only 1 patient had a serum albumin < 3.5), and serum albumin is the most influential predictor of infliximab clearance and trough achievement.…”
Section: Discussionmentioning
confidence: 99%
“…Our cohort was homogenous in terms of serum albumin (only 1 patient had a serum albumin < 3.5), and serum albumin is the most influential predictor of infliximab clearance and trough achievement. (11) Even greater heterogeneity in dose needs will likely be present in a larger, more diverse population. In addition, we demonstrated the potential challenges of achieving trough concentrations >3 μg/ml with even the most aggressive dosing (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, reliance on adult dosing in children with Crohn's disease can lead to less than 41% probability of adequate drug exposure. 24 Such significant discrepancies in drug clearance profiles between children and adults can result in early drug failure and worse outcomes for children with IBD. 24 Choosing the correct pharmacotherapy and targeting pharmacotherapy in an evidencebased way is critical to ensuring appropriate patient care aimed at optimizing future health gains.…”
Section: Second Challenge: Optimization Of Targeted Pharmacotherapymentioning
confidence: 99%